A countable fractal interpolation scheme involving Rakotch contractions - Pacurar, Cristina Maria (arXiv, 2021)
The main result of this paper states that for a given countable system of data, there exists a countable iterated function system consisting of Rakotch contractions, such that its attractor is the graph of a fractal interpolation function corresponding to the given countable system of data.